PENGARUH STRATEGI MODELLING THE WAY DISERTAI METODE DEMONSTRASI TERHADAP KETERAMPILAN MEMBACA PUISI DAN KETERAMPILAN LITERASI PADA SISWA SEKOLAH DASAR - Eliza, Metri; Malta, Malta; Junaidi, Junaidi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The initial problem was the students' low scores on the sub-chapter material reading poetry and literacy skills. The aim of the research is to find out how the modeling the way strategy accompanied by the demonstration method influences poetry reading skills and literacy skills. The research is experimental research with Randomized Control Group Only Design. In this research, the treatment that researchers will give to the experimental class is to use modeling strategies and demonstration methods, while in the control class the use of conventional learning media. With a sample of 18 students in the experimental class at SDN 03 Batu Bulek and 17 students in the control class at SDN 14 Balai Tangah. Data collection techniques use tests and performance test questionnaires. Data analysis techniques for testing normality, homogeneity, hypothesis testing, namely the t test and multivariate test to measure students' poetry reading skill level scores and literacy skills. The results of the research show that there is a difference in the influence of the modeling the way strategy accompanied by the demonstration method on poetry reading skills with conventional learning on poetry material as seen in the significant average value of poetry reading skills and the t-test results with a sig value. of 0.000; and there is also a difference in the influence of the modeling the way strategy accompanied by the demonstration method on poetry reading skills and literacy skills with conventional learning through the results of the F test with a sig value. of 0.000.